Multi Pocket System for Itinerant Barber Bag Design - Adiani, Ningroom -; An Naja, Muhammad Saif (Faculty of Civil Engeneering and Planning - ITATS, 2025)
With the increasing number of barbers in Indonesia, hybrid services can meet the needs of haircut services at the service user's place, especially those with special needs, such as: elderly with limited mobility, people with disabilities or special needs, children, and others. Itinerant barbers are also a solution to meet the needs of customers with high mobility, such as adult men who are busy with activities, so they cannot go to the barbershop.A bag is a product used to carry and store all equipment and materials for barber activities optimally. The equipment and materials are classified into 2 parts, namely priority and optional, to be adjusted to the needs of haircut activities. The bags used so far do not have this division, so they are mixed together and make it difficult for barbers when they are active. The ideal barber bag must have organized compartments to avoid damage to tools due to impacts and facilitate access to tool mobility when used and stored.The application of a multipocket system to the design of a itinerant barber bag (hybrid) is a solution for storing various equipment and supplies. Qualitative and quantitative methods are used in collecting data directly from mobile barbers and their service users through observation and surveys. Quantitative methods are used when analyzing data variables and realizing the size of the multipocket on the bag, where the size is adjusted to the needs, in order to realize the safety of the tool and the comfort of the tool user.